Between public and private. The daily life settings in the ‘domus’ of Carvalheiras - Magalhães, Fernanda; Ribeiro, Jorge Manuel Pinto; Martins, Maria Manuela (Romanitas - Revista de Estudos Grecolatinos, 2015)
The provincial Roman domus represents a privileged context to analyze the adoption of the classical architectonic and constructive models, the wealth of the urban elites and the familiar daily life, which was structured in multiple relationships of sociability between family members, between the paterfamilias and their clients or between family and servants. The house was also the context in which it was defined and stated different identities as well as the family’s social status. Based on the domus of Carvalheiras, the unique elite Roman house fully excavated in Braga, we will seek to carry out an analysis of its architecture, in order to understand the building costs and to characterize the different spaces where the relationships of the household sociability were developed.